Implantation of nasobiliary drainage in treatment of severe episodes of benign recurrent intrahepatic cholestasis (BRIC) in pediatric patients - Dądalski, Maciej; Wojciechowska, Tetiana; Ryżko, Joanna; Naorniakowska, Magda; Cielecka-Kuszyk, Joanna; Ciara, Elżbieta; Sawilska-Tańska, Małgorzata; Pawłowska, Joanna (Clinical and Experimental Hepatology, 2025)
Benign recurrent intrahepatic cholestasis (BRIC) is a rare genetic disorder characterized by episodes of intrahepatic cholestasis with varying durations and spontaneous resolutions. This article presents the use of nasobiliary drainage (NBD) in inducing remission of BRIC in our patients. We also analyze recent studies, case reports, and systematic reviews on the topic to provide an overview of the efficacy and safety of NBD in the management of BRIC. The paper is a review of a rarely (especially in children) used technique in therapy of acute episode of BRIC with a short presentation of a small series of patients in whom such a technique was applied in a single center. Our findings suggest that NBD could be a promising and effective approach for inducing remission in BRIC patients, warranting further research and larger clinical trials to better understand its long-term impact.